Identification of a 467 bp Promoter of Maize Phosphatidylinositol Synthase Gene (ZmPIS) Which Confers High-Level Gene Expression and Salinity or Osmotic Stress Inducibility in Transgenic Tobacco - Zhang, Hongli; Hou, Jiajia; Jiang, Pingping; Qi, Shoumei; Xu, Changzheng; He, Qiuxia; Ding, Zhaohua; Wang, Zhiwu; Zhang, Kewei; Li, Kunpeng (Frontiers in Plant Science, 2016)
Salinity and drought often affect plant growth and crop yields. Cloning and identification of salinity and drought stress inducible promoters is of great significance for their use in the genetic improvement of crop resistance. Previous studies showed that phosphatidylinositol synthase (PIS) is involved in plant salinity and drought stress responses but its promoter has not been characterized by far. In the study, the promoter (pZmPIS, 1834 bp upstream region of the translation initiation site) was isolated from maize genome. To functionally validate the promoter, eight 5´ deletion fragments of pZmPIS in different lengths were fused to GUS to produce pZmPIS::GUS constructs and transformed into tobacco, namely PZ1-PZ8. The transcription activity and expression pattern obviously changed when the promoter was truncated. Previous studies have demonstrated that NaCl and PEG treatments are usually used to simulate salinity and drought treatments. The results showed that PZ1-PZ7 can respond well upon NaCl and PEG treatments, while PZ8 not. PZ7 (467 bp) displayed the highest transcription activity in all tissues of transgenic tobacco amongst 5´ deleted promoter fragments, which corresponds to about 20% and 50% of CaMV35S under normal and NaCl or PEG treatment, respectively. This implied that PZ7 is the core region of pZmPIS which confers high-level gene expression and NaCl or PEG inducible nature. The 113 bp segment between PZ7 and PZ8 (-467 to -355 bp) was considered as the key sequence for ZmPIS responding to NaCl or PEG treatment. GUS transient assay in tobacco leaves showed that this segment was sufficient for the NaCl or PEG stress response. Bioinformatic analysis revealed that the 113 bp sequence may contain new elements that are crucial for ZmPIS response to NaCl or PEG stress. These results promote our understanding on transcriptional regulation mechanism of ZmPIS and the characterized PZ7 promoter fragment would be an ideal candidate for the overexpression of drought and salinity responsive gene to improve crop resistance.